PENGARUH DIGITAL LIBRARY TERHADAP MINAT BACA MAHASISWA - kholili zailani; Muhammad Husni Hamdani; Evi Fatimatur Rusydiyah (Akademika : Jurnal Teknologi Pendidikan, 2022)
The Digital Library (DIGILIB) or Digital Library has a short but tumultuous and explosive history. Some early visionaries, such as Licklider 1965, had the idea that